Novel sediment sampling method provides new insights into vertical grain size variability due to marine and aeolian beach processes. Issue 4 (8th December 2022) - van IJzendoorn, Christa O.; Hallin, Caroline; Cohn, Nicholas; Reniers, Ad J. H. M.; De Vries, Sierd
Abstract: In sandy beach systems, the aeolian sediment transport can be governed by the vertical structure of the sediment layers at the bed surface. Here, data collected with a newly developed sand scraper is presented to determine high‐resolution vertical grain size variability and how it is affected by marine and aeolian processes. Sediment samples at up to 2 mm vertical resolution down to 50 mm depth were collected at three beaches: Waldport (Oregon, USA), Noordwijk (the Netherlands) and Duck (North Carolina, USA). The results revealed that the grain size in individual layers can differ considerably from the median grain size of the total sample. The most distinct temporal variability occurred due to marine processes that resulted in significant morphological changes in the intertidal zone. The marine processes during high water resulted both in fining and coarsening of the surface sediment. Especially near the upper limit of wave runup, the formation of a veneer of coarse sediment was observed. Although the expected coarsening of the near‐surface grain size during aeolian transport events was observed at times, the opposite trend also occurred. The latter could be explained by the formation and propagation of aeolian bedforms within the intertidal zone locally resulting in sediment fining at the bed surface. The presented data lays the basis for future sediment sampling strategies and sediment transport models that investigate the feedbacks between marine and aeolian transport, and the vertical variability of the grain size distribution. Abstract : A sand scraper sampling method is developed and applied to determine the vertical grain size variability at the beach surface. The results reveal considerable variability at the millimeter‐scale that is influenced by marine and aeolian processes. The measured variability at this scale is expected to have important implications for aeolian transport processes in the intertidal zone.